Supplementing forestry field instruction with video and online dynamic quizzing. Issue 1 (29th June 2020) - Culbert, Patrick D.
Abstract: Plant identification is a critical skill for students in biological sciences, especially forestry. Many students begin with limited plant identification abilities and struggle to learn this skill. To support student learning of identification and ecological characteristics of important forest plants in an undergraduate forest ecology course at the University of British Columbia, I developed 53 videos, a companion website, and a dynamic quizzing system. The professionally produced, short videos each featured identification and ecological characteristics of a plant species, filmed in the field. The companion information website contained the embedded videos, botanical drawings, photographs, and general information for each species. The online, dynamic practice‐quizzing system allowed students to select which species they wanted to be quizzed on. Questions about those plants were then dynamically generated following several question templates, enabling students to take many practice quizzes with few or no repeated questions. Students were surveyed to gain insight into usage patterns and opinions of these resources. Student feedback was positive, and all three resources were heavily used. The videos are publicly available and have more than 43, 000 views. Although this project required significant time and financial resources to produce, I found that field instruction can be supported by optional online resources that are both appreciated and heavily used by students.